Analysis of The Influence of Institutional Ownership, Managerial Ownership, and Ownership Structure on Company Financial Performance: Case Study of Manufacturing Companies In Indonesia - Effendi, Syahril; Prima, Argo Putra (Global Financial Accounting Journal, 2023)
This research aims to analyze the impact of institutional ownership, managerial ownership, and ownership structure on the financial performance of manufacturing companies in Indonesia. Financial performance is measured using various indicators such as profitability, liquidity, and leverage. The study is based on data from a number of manufacturing companies in Indonesia during the period 2020-2022. The results of the analysis indicate that institutional ownership has a significant positive impact on the financial performance of companies, suggesting that the presence of institutional shareholders can enhance efficiency and profitability. On the other hand, managerial ownership also contributes positively to financial performance, indicating that active management participation in share ownership can drive growth and profitability. However, the research findings show that the impact of ownership structure varies depending on the financial performance indicators considered. There are significant differences in the influence of ownership structure on profitability, liquidity, and leverage of the companies. This research provides valuable insights for stakeholders, regulators, and company owners in understanding the role of institutional ownership, managerial ownership, and ownership structure in enhancing the financial performance of manufacturing companies in Indonesia. The practical implications of these findings can help companies in making better decisions regarding share ownership and financial strategies.